Description of two new species of Dascillus Latreille from southwest China (Coleoptera: Dascillidae). (1st October 2020) - Wang, Jie; Zhang, Na; Li, Shao-Bin; Jin, Zhen-Yu
ABSTRACT: Two new species of the genus Dascillus Latreille, 1797, D. chengkouensis sp. nov. and D. conchatus sp. nov. are described from Chongqing and Sichuan. The illustrations of the morphological characters and a distribution map are given. http://zoobank.org/urn:lsid:zoobank.org:pub:E6E997AB-F865-42C1-8477-28B372CA89BB